Analisis Nilai Tukar Rupiah Terhadap Eskpor Non Migas di Indonesia - Muchammad Nauval Aziqi Hidayat; Maulana Hanantyo Karlif; Sahrul Ramadan Ilham; Endang Kartini Panggiarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this article is to determine the impact of the exchange rate on Indonesia's non-oil and gas exports. Literature review is the analytical method used. The information used is secondary data, meaning it is obtained from other research findings. It is concluded that the value of Indonesia's non-oil and gas exports is negatively influenced by the exchange rate. Due to the weakening of the rupiah, a weakening exchange rate will essentially increase the value of non-oil and gas exports.